2017
DOI: 10.1101/gad.300822.117
|View full text |Cite
|
Sign up to set email alerts
|

An RNA-binding protein, Qki5, regulates embryonic neural stem cells through pre-mRNA processing in cell adhesion signaling

Abstract: Cell type-specific transcriptomes are enabled by the action of multiple regulators, which are frequently expressed within restricted tissue regions. In the present study, we identify one such regulator, Quaking 5 (Qki5), as an RNAbinding protein (RNABP) that is expressed in early embryonic neural stem cells and subsequently down-regulated during neurogenesis. mRNA sequencing analysis in neural stem cell culture indicates that Qki proteins play supporting roles in the neural stem cell transcriptome and various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 68 publications
(90 reference statements)
6
78
1
Order By: Relevance
“…As both miR-200c and miR-375 act both on the mRNA level and on translation of QKI-5, this ZEB1/miR-200/miR-375/QKI-5 regulatory loop is particularly strong, producing the strongly mesenchymal expression pattern of QKI we observed in the panel of breast cancer cell lines that we examined, paralleling the mutually exclusive expression of miR-200c and ZEB1 . Since QKI has notable functions outside of EMT, including regulating neuronal (Larocque et al, 2005;Zhao et al, 2006;Hayakawa-Yano et al, 2017), smooth muscle and vascular (Noveroske et al, 2002;Li et al, 2003;van der Veer et al, 2013;Cochrane et al, 2017) cell function, and alternative splicing programmes during muscle cell (Hall et al, 2013) and monocyte (de Bruin et al, 2016a) differentiation, we propose that the ZEB1/miR-200c/miR-375/QKI-5 pathway may influence splicing outcomes that impact a broad range of cell differentiation contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As both miR-200c and miR-375 act both on the mRNA level and on translation of QKI-5, this ZEB1/miR-200/miR-375/QKI-5 regulatory loop is particularly strong, producing the strongly mesenchymal expression pattern of QKI we observed in the panel of breast cancer cell lines that we examined, paralleling the mutually exclusive expression of miR-200c and ZEB1 . Since QKI has notable functions outside of EMT, including regulating neuronal (Larocque et al, 2005;Zhao et al, 2006;Hayakawa-Yano et al, 2017), smooth muscle and vascular (Noveroske et al, 2002;Li et al, 2003;van der Veer et al, 2013;Cochrane et al, 2017) cell function, and alternative splicing programmes during muscle cell (Hall et al, 2013) and monocyte (de Bruin et al, 2016a) differentiation, we propose that the ZEB1/miR-200c/miR-375/QKI-5 pathway may influence splicing outcomes that impact a broad range of cell differentiation contexts.…”
Section: Discussionmentioning
confidence: 99%
“…We find here that miR‐200 exerts a widespread influence on alternative splicing during EMT, through its strong regulation of QKI. QKI is a member of the STAR family of RBPs and has been reported to have diverse functions in mRNA stability (Larocque et al , ; Zhao et al , ) and translation (Saccomanno et al , ; de Bruin et al , ), miRNA processing (Wang et al , , ) and alternative splicing (Hall et al , ; van der Veer et al , ; Zong et al , ; de Bruin et al , ; Darbelli et al , ; Fagg et al , ; Hayakawa‐Yano et al , ). We have recently shown that QKI can promote circular RNA formation during EMT (Conn et al , ), although the functional consequences of QKI in EMT remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to focus on QKI-6 for CLIP experiments for two reasons: firstly, QKI-5 is predominantly nuclear but QKI-6 and QKI-7 are both nuclear and cytoplasmic, and we posited that cytoplasmic isoforms are more likely candidates for translation regulation. Secondly, QKI-6 is expressed earlier in development than QKI-7 28 suggesting an importance in early neuronal circuitry formation, a function largely governed by astrocytes. Finally, QKI-7 was had more variable intensity of expression across astrocytes( Fig.1A).…”
Section: Qki-6 Protein Binds Translationally Regulated Mrnas In Astromentioning
confidence: 99%
“…This large intronic signal is likely due to the splicing and nuclear retention functions of the nuclear isoform, QKI-5 20,32 . Indeed, a recent QKI-5 specific CLIP experiment in E14.5 mouse brain, where QKI-5 is highly expressed in neural stem cells, showed 41.6% of binding sites in introns 28 . Recent work in C. elegans emphasized the importance of 5'UTR QKI motifs 33 , yet we found very few(<1%) QKI-6 peaks in the 5'UTR of mouse brain transcripts( Fig.…”
Section: Qki-6 Protein Binds Translationally Regulated Mrnas In Astromentioning
confidence: 99%
“…Because monocytes are also osteoclast precursors, it prompted us to consider a role for QKI5 expression/modulation in osteoclastogenesis. QKI5 has been mainly studied in the context of brain development and has been described as a crucial regulator of embryogenesis and central nervous system (CNS) development . Nevertheless, QKI5 has never been studied in the context of bone biology, especially in osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%